675 FUNDOPLICATION VERSUS ORAL PROTON PUMP INHIBITORS FOR GASTROESOPHAGEAL REFLUX DISEASE: A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED CLINICAL TRIALS. (17th September 2021) - Tristão, Luca Schiliró; Tustumi, Francisco; Tavares, Guilherme; Datrino, Letícia Nogueira; Serafim, Maria Carolina Andrade; Orlandini, Marina Feliciano; Santos, Clara Lucato; Bernardo, Wanderley Marques
Abstract: : Gastroesophageal reflux disease (GERD) is a widely studied and highly prevalent condition. However, few is reported about the exact efficacy and safety of fundoplication (FPT) compared to oral intake proton-pump inhibitors (PPI). This systematic review and meta-analysis of randomized clinical trials (RCT) aims to compare PPI and FPT in relation to the efficacy, as well as the adverse events associated with these therapies. Methods: This systematic review was guided by PRISMA statement. Search carried out in June 2020 was conducted on Medline, Cochrane, EMBASE and LILACS. The inclusion criteria were (I) patients with GERD; (II) Randomized clinical trials, comparing oral intake PPI with FPT; (III) relevant outcomes for this review. The exclusion criteria were (I) reviews, case reports, editorials and letters (II) transoral or endoscopic FPT (III) studies with no full text. No restrictions were set for language or period. Certainty of evidence and risk of bias were assessed with GRADE Pro and with Review Manager Version 5.4 bias assessment tool. Results: Ten RCT were included. Meta-analysis showed that heartburn (RD = −0.19; 95% CI = −0.29, −0.09) was less frequently reported by patients that underwent FPT. Furthermore, patients undergoing surgery had greater pressure on the lower esophageal sphincter than those who used PPI (MD = 7.81; 95% CI 4.79, 10.83). There was no significant difference between groups in the percentage of time with pH less than 4 in 24 hours, sustained remission and Gastrointestinal Symptom Rating Scale. Finally, FPT did not increase significantly the risk for adverse events such as postoperative dysphagia and impaired belching. Conclusion: FPT is a more effective therapy than PPI treatment for GERD, without significantly increasing the risk for adverse events. However, before indicating a possible surgical approach, it is extremely important to correctly assess and select the patients who would benefit from FPT, such as those with severe erosive esophagitis, severe respiratory symptoms, low adherence to continuous drug treatment and patients with non-acid reflux, to ensure better results.